Reinforcing Factor Analysis on Breast Self-Examination (BSE) - Dede, Dede Waslia (JURNAL KESEHATAN KARTIKA, 2021)
Breast cancer is a major issue of women's health in the world, especially in developing countries which have limited resources such as in Indonesia. The reason is because of the lack of an effective screening program to detect pre-cancerous and cancer conditions at early stage including treatment before a further invasive process. Early detection of breast cancer needs to be done to reduce mortality rate. Breast self-examination can find breast cancer up to 75-85% if done regularly. Willingness to perform breast self-examination is one form of behavior which is influenced by many factors,one of which is reinforcing. The aim of the research is to identify the relationship between reinforcing factors and breast selfexamination (BSE). The method used is a quantitative with a cross sectional approach. The populations were reproductive age women with a sample of 120 people by random sampling technique. Data collection was done through direct interview using questionnaire. The results concluded that from 120 respondents, most respondents (74.2%) perform breast selfexamination. The reinforcing factors associated with breast self-examination are friends support (Pvalue 0,000), husband/ family support (Pvalue 0,000), and health personnel support (Pvalue 0,000).The most related reinforcing factor is husband / family support.